2016
DOI: 10.1007/978-1-4939-6670-7_1
|View full text |Cite
|
Sign up to set email alerts
|

The Immortal Senescence

Abstract: Activation of oncogenic signaling paradoxically results in the permanent withdrawal from cell cycle and induction of senescence (oncogene-induced senescence (OIS)). OIS is a fail-safe mechanism used by the cells to prevent uncontrolled tumor-growth and, as such, it is considered as the first barrier against cancer. In order to progress, tumor cells thus need to first overcome the senescent phenotype. Despite the increasing attention gained by OIS in the past 20 years, this field is still rather young due to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 148 publications
(189 reference statements)
0
6
0
2
Order By: Relevance
“…As the exit from the cell cycle in senescent cells is commonly established and maintained through the activation of tumor suppressor pathways centered on p53 and/or pRb [ 28 ], it was rapidly recognized that cellular senescence represented a cell-intrinsic mechanism that limits the proliferation of damaged and potentially cancerous cells [ 4 ]. Thus, much like apoptosis, cellular senescence acts as a barrier that cells must overcome in order to become immortalized and transformed, explaining the high frequency at which these pathways become disrupted in human cancers [ 29 , 30 ].…”
Section: Cellular Senescence In a Nutshellmentioning
confidence: 99%
“…As the exit from the cell cycle in senescent cells is commonly established and maintained through the activation of tumor suppressor pathways centered on p53 and/or pRb [ 28 ], it was rapidly recognized that cellular senescence represented a cell-intrinsic mechanism that limits the proliferation of damaged and potentially cancerous cells [ 4 ]. Thus, much like apoptosis, cellular senescence acts as a barrier that cells must overcome in order to become immortalized and transformed, explaining the high frequency at which these pathways become disrupted in human cancers [ 29 , 30 ].…”
Section: Cellular Senescence In a Nutshellmentioning
confidence: 99%
“…Aging is caused by a variety of mechanisms, including oncogenic signals, telomere shortening, and DNA damage. Induction of aging by oncogenes is one of the important mechanisms of aging (Bianchi-Smiraglia et al 2017). Epigenetic silencing of gene loci encoding aging pathway effectors usually occurs in normal dividing cells.…”
Section: Jmjd3 In Aging Related Diseasesmentioning
confidence: 99%
“…Alternatively, sif KD or sick KD FSCs may be rendered quiescent or senescent, unable to interpret feeding-dependent signals to enable normal FSC function. Given the propensity of oncogenes to initially induce senescence ( Bianchi-Smiraglia et al, 2017 ; Zhu et al, 2020 ) and the importance of quiescent states in cancer risk ( Paul et al, 2022 ), it may be of high interest to understand the phenotype observed in sif KD and sick KD FSCs as a mechanistic target to prevent transformation.…”
Section: Discussionmentioning
confidence: 99%